"Weight of the World" and "I Want Them to Know": Skilled Nursing Facility Administrators' Perspectives on COVID-19 in Research Poems. Issue 2 (17th February 2023) - Jen, Sarah; Jeong, Mijin; Smith, Madeline
ABSTRACT: COVID-19 has had a drastic, long-lasting impact on skilled nursing facilities (SNFs), forcing communities to continuously adapt to rapidly changing guidelines, restrictions, and challenges. In spring 2020, we conducted a sequential mixed-methods study with administrators of SNFs in the Midwest to understand the experience of administrators, staff, and residents during the pandemic. We collected 60 surveys with open-ended items related to the impact of the pandemic on communities as a whole, staff, and residents. Survey findings informed supplemental interviews with six administrators working in diverse regions. Due to the affective nature of the data, we present the findings in two found poems, which emphasize the lyrical, emotional, and poignant aspects of the participant voices. The first poem, Weight of the World, captures the struggle to adapt during the transition into the pandemic and its negative impacts on the lives of residents and their families. The second, I Want Them to Know, describes the resiliency with which administrators and staff responded to adversity while maintaining motivation to continue the work in the midst of unprecedented challenges. The two poems offer contrasting or balancing narratives of struggle and survival during the pandemic era.